DEVELOPING HUMAN CAPITAL TO ENHANCE THE COMPETITIVENESS OF HIGHER EDUCATION INSTITUTIONS (International Congress on Economics, Management and Business Studies, 2026)
This thesis article examines how the development of academic human capital can strengthen the competitiveness of higher education institutions (HEIs), with particular attention to the case of Uzbekistan. The research argues that institutional competitiveness is not determined only by infrastructure or student enrolment expansion; it is increasingly shaped by the quality, motivation, research productivity, digital competence, and international engagement of academic staff. Using a mixed desk-research design, the paper synthesizes human capital theory, university competitiveness frameworks, ranking methodologies, and national statistics. The analysis shows that Uzbekistan has made rapid progress in expanding higher education access: the number of HEIs increased from 127 in 2020/2021 to 222 in 2024/2025, while students reached about 1.43 million in 2024/2025. However, the growth of academic staff and their research capacity must accelerate to transform quantitative expansion into quality-based competitiveness. The proposed Human Capital-Competitiveness Model links faculty development, digital and research skills, industry cooperation, and internationalization into a single institutional management framework.
Keywords: Academic human capital; higher education; university competitiveness; faculty development; Uzbekistan; innovation capacity.